"Infraestructuras inteligentes y su incidencia en el desempeño de los usuarios internos y externos del gobierno autónomo descentralizado de la provincia de los Ríos. Año 201. Centro inteligente de atención al ciudadano" - Aguirre Varas, Jacinto Roldán (2015)
This Thesis is based on smart infrastructure and its impact on the performance of internal and external users of the Government Autonomous Decentralized of Los Ríos. 2013. "smart Center for citizen services". Decentralized Autonomous Government of the Province de los Rios, is a government institution that provides services, aims to formulate and execute plans, programs and projects to ensure social, economic and productive development of the province and the country. The institution has its main building in the city of Babahoyo and a unit in the city of Quevedo in the province of Los Rios, his methodology does not have manual processes established and because of the complete renovation of their dependence on the city Babahoyo, administrators and authorities want to turn this institution carry a model of intelligent infrastructure allowing them to better serve the riosense citizenship. Lacking rules and controls business processes arises the following question How intelligent infrastructure affects the Process Management System in Building Government Autonomous Decentralized of Los Ríos? The purpose is to develop an intelligent citizen services center where internal and external users will ease in managing their transactions, the company will gain in comfort, because you can disregard all the logistics related to the cumbersome displacement and loss of time to address the status of any process; because with a single call or search by a ticket from the smart center, internal systematization of it will take care of all management is carried out in the institution. This makes a comprehensive service support technology and workflow systems and documents.Featured in intelligent infrastructure companies already use similar methods in process management system, an ambitious undertaking in trying to service together with comfort and efficiency cannot be underestimated technology today in our hands.....................................................................